Poetische Brücken über sprachliche Lücken. Kompositabildung und Gapping in Peter Handkes «Bildverlust» und «Kali» analysiert mit corpuslinguistischen Methoden: [Poetic Bridges over Language Gaps. Compound Creation and Gapping in Peter Handke’s «Crossing the Sierra de Gredos» and «Kali» Analyzed with Corpus Linguistics Methods] (Studia austriaca, 2017)
This paper investigates creative word formation and especially the word formation method of gapping in Peter Handke’s literature by employing corpus linguistic methods. His novel Der Bildverlust oder Durch die Sierra de Gredos (2002; transl. Crossing the Sierra de Gredos, 2007) is investigated as an exemplary work of the author’s late creative development and compared to the novella Kali. Eine Vorwintergeschichte (2007) in order to test the findings. The linguistic analysis is framed and contextualized with a literary criticism approach, thus offering new perspectives for both disciplines.